The remodelling of tibial trabecular bone in spontaneous animal model of osteoarthritis - Akman, Akma Azmiera; Talib, Ain Aisyah; Md Yusof, Azirah; Khalid, Kamarul Ariffin; Yusof, Nurul Asyiqin; Abdul Ghani, Radiah; Hamdan, Asmah Hanim; Zamli, Zaitunnatakhin (2018)
Osteoarthritis (OA) is a common degenerative joint disease among elderly population. Previous studies have shown that OA is associated with the subchondral bone remodelling. However, none of these studies focuses on the trabecular bone (Tb) remodelling in the epiphyseal region of tibia. Hence, the present study aims to determine the mineral apposition rate (MAR), mineralising surface (MS) and bone formation rate (BFR) of Tb Dunkin Hartley (DH) guinea pigs, and its association with microscopic score of OA. The DH was administered with 20 mg/kg of calcein dye at 9 and 2 days prior to euthanasia. The tibia were then collected at 10, 20 and 30 weeks of age. Histomorphometry and histopathology analyses were conducted to quantify the parameters of Tb remodelling and microscopic OA score, respectively. The data showed that the MAR, MS and BFR were higher in the medial side (versus lateral side) of the tibia (p ≤ 0.05), and increased between 10 and 20 weeks of age. However, at the final time point, these parameters were significantly decreased (p ≤ 0.05), and became lower in the medial than the lateral side of Tb. A strong negative correlation was observed between the BFR and microscopic OA scores (r = -1.0, p ≤ 0.01), suggesting that the Tb loss dominates the late stage of OA.